2022
DOI: 10.1111/hiv.13391
|View full text |Cite
|
Sign up to set email alerts
|

Immune restoration affects 10‐year survival in people living with HIV/AIDS

Abstract: Introduction In recent years, a reduction in the life expectancy gap between people living with HIV (PLWH) and the general population has been observed, irrespective of CD4 lymphocyte count, due to widespread access to antiretroviral treatment. The increase in the life expectancy of PLWH has increased awareness of both the ageing process and gender discrepancies in immune restoration and survival. Materials and Methods Longitudinal data were collected for 2240 patients followed up at the Hospital for Infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although the introduction of antiretroviral therapy (ART) has achieved viral suppression and subsequent immune reconstitution in most people living with HIV-1 (PLWH), increased risks of chronic AIDS-related illnesses associated with aging are still challenging in this population ( 1 ). Nevertheless, 10-30% of PLWH suffer from poor immune recovery despite prolonged successful suppressive ART, which further speeds up the disease progression and contributes to increased mortality, referred to as “immunological non-responders” (INRs) ( 1 , 2 ). Though there was no unified standard for INRs, the CD4+T cell count could not reach 350 cells/μl or 500 cells/μl after years of ART was used in some reports ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the introduction of antiretroviral therapy (ART) has achieved viral suppression and subsequent immune reconstitution in most people living with HIV-1 (PLWH), increased risks of chronic AIDS-related illnesses associated with aging are still challenging in this population ( 1 ). Nevertheless, 10-30% of PLWH suffer from poor immune recovery despite prolonged successful suppressive ART, which further speeds up the disease progression and contributes to increased mortality, referred to as “immunological non-responders” (INRs) ( 1 , 2 ). Though there was no unified standard for INRs, the CD4+T cell count could not reach 350 cells/μl or 500 cells/μl after years of ART was used in some reports ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Items assessing study attrition showed the highest risk of bias. The overall risk of bias in the included studies was high (n=7; 35%) ( 28 , 30 , 31 , 36 , 37 , 40 , 43 ), moderate (n=11: 55%) ( 9 , 18 , 19 , 21 , 29 , 32 , 33 , 35 , 38 , 39 , 41 ), or low (n=2; 10%) ( 20 , 42 ). Nearly all included studies (n=18; 90%) ( 9 , 18 , 19 , 21 , 28 33 , 35 41 , 43 ) lacked a description of the lost and censored participants, their characteristics, and the methodology for statistical imputation of the missing values.…”
Section: Methodsmentioning
confidence: 99%
“…Low CD4+/CD8+ ratio (<0.3) correlates with higher risk of non–AIDS-defining events and mortality ( 15 17 ). Restoration of immunologic function, measured by increases in absolute CD4+ T-cell count to >200 cells/mm 3 and CD4+/CD8+ ratio to >0.45, is an important treatment goal for all people living with HIV, particularly those with low CD4+ T-cell count ( 16 20 ).…”
Section: Introductionmentioning
confidence: 99%